Design Hybrid Nanogel of Prednisolone for Topical Application, Preparation, Characterization, In-vitro and Ex-vivo Evaluation: Hybrid Nanogel of Prednisolone - Drais, Hayder Kadhim (Iranian Journal of Pharmaceutical Sciences, 2023)
The prednisolone was very slightly soluble in water. It was a curative agent against oral recurrent aphthous stomatitis. The main objective of this study is to design, prepare, and evaluate a hybrid nanogel of prednisolone as a topical dosage form to increase prednisolone solubility, stability, and therapeutic activity. The microwave-based method prepared nine prednisolone lipid polymer hybrid nanocarriers LPHNs formulations (H1-H9). The conventional prednisolone gel (G) was prepared by solvent diffusion. The H1-H9 was evaluated thermodynamically and entered into characterization processes. The hybrid nanogels HN1-HN9 formulations were tested for various evaluations. All the H1-H9 formulations showed high thermodynamic stability and nanosized globules, low polydispersity index, acceptable surface charge, entrapment efficiency, and drug loading. The evaluation processes indicate stable organoleptic properties, high homogeneity, fair pH and spreadability coefficient values with plastic viscosity and no erythemic reaction. The profile of prednisolone release and permeability coefficient (cm/min) was significantly higher (p-value <0.05) for HN3 and significantly lower (p-value < 0.05) for conventional prednisolone gel (G). The optimized HN1-HN9 formulations were promised drug delivery systems for treating recurrent aphthous stomatitis and a wide variety of oral lesions in addition to local and transdermal delivery of various therapeutic agents and cosmetics.